THE WEIGHT OF ABSENCE: MEMORY, TRAUMA, AND TESTIMONIAL FICTION IN BERNARDO KUCINSKI’S K. – RELATO DE UMA BUSCA - Moebid, Abdulkareem Jwaid (Academic Journal Research, 2025)
Objective:  This article focuses on the intersections between memory, trauma, and story in a hybrid novel that interlaces fiction with first-hand reportage and history, K.'s - Relato de uma busca. The piece narrates the short life of a young woman, as much as the Brazilian dictatorship (1964-1985), and I’m interested in how this relation between fragments and subjectivity constitutes an ethics to think dictatorship. It tells the story of a father who never stops looking for his daughter, who disappears without a goodbye. But it is also a lament and a cultural intervention in public and private memory. This present study belongs to the broader literary tradition of testimonial fiction, and also to a desire to ‘play’ narrated forms capable of “recuperating erased histories” (Hutcheon). Method: The analysis tries to observe how Kucinski creates a literary space where trauma and lack are shown with compassion. Adopting a qualitative research method of textual analysis, the essay will explore structure, voice, temporal dislocation, and the role and making of fictional documents in the novel. These approaches are based on trauma theory and narratology, which show how fragmentation, second-person address and polyphony are results of a contested experience of political violence. Results: The evidence I have presented above suggests that the fragmentation of the plot as well as the chronological sequence, show how the memories, unintelligible, left by historical moments, twisted man’s faculty of instantly recalling the past in his head; but the range of evidence of the thematic convention to the fact of achievement in artwork is to be direct. Polyphonic voice is the text that we match up lines against received history and rattles its foundation. Absence isn't indicative of an absence at all but represents independent memories that are worthy to be ethical witnesses. Novelty: The study therefore concludes that K. is both a testimony and a form of resistance turning silence into a politically and emotionally saturated liter¬ary presence. It highlights the significance of narratives to the maintenance of collective memory in post-authoritarian situations.